Implementasi Metode Talaqi dalam Hafalan Alquran dengan Pendekatan One Day One Ayat pada Sekolah Menengah Pertama Terpadu Al-Farabi Deli Serdang - Siti Sahrapmahita Saragih; Danny Abrianto; Tumiran Tumiran (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2026)
This study examines the implementation of the talaqi method in Qur’an memorization integrated with the One Day One Ayat approach at Al-Farabi Integrated Junior High School, Deli Serdang, in response to the need for effective, developmentally appropriate tahfizh strategies at the secondary level. The study addresses how the combined approach is implemented, the outcomes it produces, and the challenges encountered in practice. Employing a qualitative case study design, data were collected through classroom observations, in-depth interviews with teachers and administrators, and analysis of program documentation. The findings indicate that the tahfizh program is systematically organized through grade-based memorization targets, daily talaqi sessions complemented by muraja’ah, and periodic evaluations. This implementation contributes to improved accuracy of recitation, stronger memorization (mutqin), and increased student discipline, supported by teacher commitment, a conducive Islamic school culture, standardized mushaf, and parental involvement. Nevertheless, limitations in instructional time, variations in students’ memorization abilities, and uneven family support remain significant challenges. The study argues that integrating talaqi with the One Day One Ayat approach offers a pedagogically sound and sustainable model for Qur’an memorization in Islamic secondary education.